ANALYSIS OF THE CURRENT OVERVIEW OF USE AND INTERACTION: BLIND USERS AND E-LEARNING PLATFORMS - Lisboa, Isolda Veronese Moniz Vianna; Barroso, João Manuel Pereira; de Jesus Vilela da Rocha, Tânia (Seven Editora, 2025)
E-Learning platforms have the potential to improve the quality of learning and increase access to education, as long as they are attentive to the needs of diverse users. One of the motivations for this research was the potential to contribute by investigating the experience of blind users interacting with online educational content. This study aimed to investigate the accessibility profile of content on Brazilian distance learning institutions’ e-learning websites from the perspective of blind students interacting with online educational content. Is the user experience of blind students interacting with educational content on e-Learning platforms positive? Are there limitations to achieving their goals and meeting their needs? We used online qualitative and quantitative questionnaires to collect data. We identified difficulties experienced by blind students in their interactions and the need for greater awareness among those involved in distance learning about these difficulties. DOI: https://doi.org/10.56238/sevened2025.029-070